Haplotype and genotype effects of the F7 gene on circulating factor VII, coagulation activation markers and incident coronary heart disease in UK men - Ken-Dror, Gie (2010)
BACKGROUND: Evidence for the associations of single nucleotide polymorphisms (SNPs) in the F7 gene and factor VII (FVII) levels and with risk of coronary heart disease (CHD) is inconsistent. We examined whether F7 tagging SNPs and haplotypes were associated with FVII levels, coagulation activation markers (CAMs) and CHD risk in two cohorts of UK men. METHODS: Genotypes for eight SNPs and baseline levels of FVIIc, FVIIag, and CAMs (including FVIIa) were determined in 2773 healthy men from the Second Northwick Park Heart Study (NPHS-II). A second cohort, Whitehall II study (WH-II, n=4055), was used for replication analysis of FVIIc levels and CHD-risk. RESULTS: In NPHS-II the minor alleles of three SNPs (rs555212, rs762635, and rs510317; haplotype H2) were associated with higher levels of FVIIag, FVIIc, and FVIIa, while the minor allele for two SNPs (I/D323, and rs6046; haplotype H5) were associated with lower levels. Adjusted for classical risk factors, H2 carriers had a CHD Hazard Ratio of 1.34 (CI 95%: 1.12–1.59; independent of FVIIc), while H5 carriers had a CHD-risk of 1.29 (CI 95%: 1.01–1.56; not independent of FVIIc) and significantly lower CAMs. Effects of haplotypes on FVIIc levels were replicated in WH-II, as was association of H5 with higher CHD-risk (pooled-estimate OR 1.16 [1.00–1.36], P=0.05), but surprisingly, H2 exhibited a reduced risk for CHD. CONCLUSION: tSNPs in the F7 gene strongly influence FVII levels. The haplotype associated with low FVIIc level, with particularly reduced functional activity, was consistently associated with increased risk for CHD, while the haplotype associated with high FVIIc level was not.